2016
DOI: 10.1249/mss.0000000000001055
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention to Encourage Physical Activity in Infants and Toddlers

Abstract: An early life intervention targeting improvements in child and parent physical activity as part of a wider obesity prevention initiative had little effect on physical activity at 2 yr of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…Four studies reported that the intervention dose was insufficient to impact on children's physical activity or on any of the mechanisms targeted . Three of the studies cited insufficient frequency or duration of intervention sessions (four group sessions for parents over 18 months ; 60‐min physical activity session for children once a week ; 15–20‐min physical activity session 4 days per week ), and the other postulated the short duration of the intervention program (4 months ) Despite education being the most commonly targeted mechanisms across most contexts, there was no evidence that this strategy was effective at changing children's physical activity levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported that the intervention dose was insufficient to impact on children's physical activity or on any of the mechanisms targeted . Three of the studies cited insufficient frequency or duration of intervention sessions (four group sessions for parents over 18 months ; 60‐min physical activity session for children once a week ; 15–20‐min physical activity session 4 days per week ), and the other postulated the short duration of the intervention program (4 months ) Despite education being the most commonly targeted mechanisms across most contexts, there was no evidence that this strategy was effective at changing children's physical activity levels.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies included in the realist review mentioned the intervention dose as insufficient to impact on mechanisms or elicit a change in children's physical activity . Two of the studies reported this in terms of the number of daily sessions of physical activity required and the other discussed the short duration of the intervention program .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were four demographic variables that correlated with tummy time from 10 articles 191 (Table 3). Age had a positive correlation with tummy time from six studies (Rocha and 192 Tudella, 2008, Majnemer and Barr, 2006, Hesketh et al, 2015, Carmeli et al, 2009, 193 Bridgewater and Sullivan, 1999, Salls et al, 2002a and an unclear association in two studies 194 (Davis et al, 1998, Moir et al, 2016. Older parents and low parent education level was 195 found to have a negative correlation (van Vlimmeren et al, 2007, Majnemer andBarr, 2006).…”
Section: Demographic Variables 190mentioning
confidence: 96%
“…Time spent, tolerance of, age when first experienced and parent attitudes/knowledge of tummy time was not measured objectively in any articles and subjectively in nine articles, 177 primarily by proxy-report questionnaire, log, or interview (Carmeli et al, 2009, Davis et al, 178 1998, Hesketh et al, 2015, Jennings et al, 2005, Moir et al, 2016, Ricard and Metz, 2014, 179 Salls et al, 2002a, van Vlimmeren et al, 2007, Zachry and Kitzmann, 2011. The ability of 180 the infant to move whilst on the stomach was only measured objectively in seven articles, 181 primarily by validated assessment tools (e.g., prone AIMS scale, Chailey level of abilities 182 scale, prone position) (Bartlett and Fanning, 2003, Bell and Darling, 1965, Bridgewater and 183 Sullivan, 1999, Majnemer and Barr, 2006, Rocha and Tudella, 2008, Salls et al, 2002a and 184 direct observation (Horowitz and Sharby, 1988).…”
mentioning
confidence: 99%